Forensic analysis of note and journal applications. (March 2022) - Shin, Sumin; Kim, Giyoon; Kim, Soram; Kim, Jongsung
Abstract: As the rate of smartphones into the general population has increased, apps that provide a wide range of functions have been developed. The usage records can remain within the app, and are a significant target for analysis from a digital forensic perspective. However, some apps protect app data by providing security features. From the perspective of digital forensic investigation, there is a need for research into apps that provide security features, so that investigators can efficiently collect forensically useful data. In this study, we analyzed the secret values used for locking, and the methods for storing user-created content of 56 note and journal apps that provide security features within the app. We found that 95% of apps that provide security features store users' data insecurely. We propose methods of acquiring a password from another app, using the user's secret value that can be obtained within the app. Highlights: Identifing the security settings provided by each app. Identifing the user secret value used for security settings, and the storage location and storage type of the content. Analyzing vulnerabilities of note and journal apps. Providing decryption methods for encrypted app data.